Landform dynamics and evolution in Romania - Radoane, Maria; Vespremeanu-Stroe, Alfred (Springer, 2017)
New and innovative scientific theories, discussion and explanations are presented on landform dynamics and evolution in Romania along with a comprehensive understanding of the geomorphological processes shaping the large variety of Romania?s landscape. Thematically arranged the book deals with landform dynamics of specific relief types: glacial and periglacial, denudational, fluvio-denudational, fluvial, karst and coasts, as well as sediment fluxes, geomorphic hazards and risks. The authors are key scientists and researchers in the field and offer innovative views on research methods and concepts applied to the topics in question. This work will be of interest to students and researchers in geography, geomorphology, geology, environmental science, paleoclimatology and soil science as well as policy and decision-makers in spatial planning.- Resumé vydavatel
Keywords: geomorfologie -- Rumunsko; geografie -- Rumunsko; geomorphology -- Romania; geography -- Romania; elektronické knihy; sborníky; electronic books; papers of several authors